PENGARUH KOMPENSASI DAN PENGAWASAN PIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASSET DAERAH KABUPATEN BATANG - Prabowo, Dhista Adi; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2014)
This research is motivated employee discipline in the Batang DPPKAD Year 2013. Low labor discipline is because the agency has not provided compensation and oversight of the leadership is good and right. This study aimed to examine the effect of compensation and oversight leadership to discipline the employee DPPKAD Batang. This study uses Slovin formula with sample was 50 people from Batang DPPKAD employee population of 100 people. The analytical method used is multiple linear regression. The results of the study found that the following regression equation: Y = 0.345 X1 + 0.560 X2. Based on the analysis of statistical data, indicators - indicators in this study is valid and reliable. In the classical assumption test, regression model-free multicollinearity, heteroscedasticity and does not occur in normal distribution. The greatest variable is the variable leadership oversight of 0.560, while the smallest variable is the variable compensation of 0,345. The results of the study found that all independent variables are positive and significant effect on the dependent variable.